Reducing flight time during running decreases tibial-fibular strains in male runners: a finite element analysis - Khassetarash, A.; Nigg, B. M.; Edwards, W. B. (Journal of Biomechanics, 2025)
Reducing strains within the tibia and fibula during running may reduce the risk of stress fractures. We examined the effect of reduced flight time during running (i.e., grounded running) on finite-element predicted bone strains within the tibia-fibula complex. Nine physically active males ran on an instrumented treadmill at 2.2 m/s using a preferred and reduced flight time technique in a randomized order. Three-dimensional force and motion capture data were recorded during running and a computed tomography image was subsequently acquired for the participant`s left leg. An inverse-dynamics-based musculoskeletal modeling workflow was used to calculate bone-on-bone contact and muscle forces during the stance phase of running. These forces served as inputs to a participant-specific finite-element model to estimate peak bone strains and strained volume (i.e., the volume of bone experiencing strains above a specific threshold) within the tibia-fibula complex. Guided attempts to reduce flight time was successful with an 18 ms (95 % CI: 12 ms, 25 ms; p < 0.001) reduction in flight time. Reducing flight time was associated with significant reductions in peak tibial/fibular strains (17 % lower; 95 % CI: -7.1 %, -25.0 %; p = 0.002) and strained volume (35 % lower; 95 % CI: -13.57 %, -50.87 %; p = 0.007). We conclude that guided attempts to reduce flight time significantly reduces strains in the tibia and fibula during treadmill running at a fixed speed. These results suggest that grounded running may be a viable technique to reduce musculoskeletal loading and stress fracture risk, particularly in slow runners and those runners coming back from injury.